REFRAMING ENVIRONMENTAL DISCOURSE IN SCIENCE-BASED ENGLISH E-BOOKS: AN ECOLINGUISTIC ANALYSIS IN INDONESIAN JUNIOR HIGH SCHOOLS - Abd Syakur; Ni Wayan Sartini; Hilman Fikri; Ika Rahmania (Linguists : Journal of Linguistics and Language Teaching, 2026)
Background of study: Despite the increasing integration of English-language e-books into Indonesian science classrooms, research remains limited on how environmental issues are represented in these materials, particularly from an ecolinguistics perspective. Existing studies tend to focus on general language proficiency or content comprehension, often overlooking the subtle ways in which language shapes learners' understanding of ecological concepts and human–nature relationships. Aims and scope of paper: This study aims to investigate the representation of environmental discourse in science-based English e-books used by junior high school students in Indonesia, uncovering the linguistic patterns that construct or obscure ecological awareness. Methods: Employing a qualitative research design with content analysis, the study analyzed a purposive sample of five widely adopted e-books from SMPN 6 Malang, selected based on curriculum relevance and classroom use frequency. Data were collected by systematically coding procedural texts for lexical choices, thematic framing, and syntactic structures that reflect ecological perspectives. Result: The findings reveal that while several texts integrate environmentally conscious vocabulary and encourage inquiry into natural processes, there are frequent instances of anthropocentric framing and implicit prioritization of human utility over ecological balance, suggesting a tension between promoting awareness and maintaining conventional procedural orientations. Conclusion: These nuances indicate that while e-books offer opportunities to foster ecological literacy, careful selection and supplementation are required to enhance learners' authentic understanding of the environment.